Study of digital timing adjustment techniques - Lee, Yeok Boon. (2009)
Interpolation of signal samples in a digital receiver must be performed if sampling is not synchronized to the incoming data symbols. This report is based on the theoretical background for digital interpolation and its control method in a data receiver introduced in [1]. The scope of this project includes the verification of the Farrow structure Finite Impulse Response Filter (FIR) and its control method using Numerically Controlled Oscillator (NCO). This FIR structure was found to be particularly convenient in practical hardware.